Information framing effects on diet choices among Chinese urban residents - Chen, Kevin Z.; Yu, Luyun; Lin, Wen; Ortega, David L. (Wiley, 2026)
Unhealthy diets have become a leading contributor to death and disability globally. The current Chinese diet falls short of a healthy diet, including too much meat, oil, salt, and sugar while having insufficient levels of whole grains, fruits, nuts, and milk. Transforming Chinese dietary patterns has become urgent. This paper compares the effectiveness of information framing effects on enhancing Chinese consumers' healthy diet choices, varied by information content, source, and presentation. The survey is conducted across six Chinese cities, with a sample of 3150 urban consumers. Chinese consumers' healthy diet choices are measured using an online discrete choice experiment. Four different diet patterns were used to label each of the product alternatives in the experiment, which varied in taste and cost. Results reveal that compared to positive information; negatively framed healthy information is more effective in increasing Chinese consumers' valuations for healthy diets. Consumer valuation of a healthy whole diet is significantly enhanced when the information is from social celebrities, compared to information from a scientific source. Moreover, when health information is disclosed via social media, its effectiveness in promoting healthy diet choices is significantly reduced. Our findings have implications for designing and implementing nutrition policies and programs in China and other developing countries.